Toxocara seroprevalence and childhood asthma among Malaysian children - Chan, P.W.K.; Anuar, A.K.; Fong, M.Y.; Debruyne, J.A.; Ibrahim, J. (Blackwell Publishing, 2001)
Background: The larva of Taxocara spp., a common animal roundworm, may infect non-compatible hosts, causing a profound immunological reaction with marked eosinophil and IgE responses, not unlike in atopy. In this study. we determined the seroprevalence of Toxocara exposure in 66 asthmatic and 58 non-asthmatic children. Methods: Exposure to Toxocara was determined by examining the serum samples of the children for specific IgG antibodies to L2 Toxocara larvae, using a commercially available diagnostic kit. Results: There was no significant difference in the mean age, sex, social class, residence type and presence of domestic pets at home between the two children groups. Children with bronchial asthma were observed to have higher Toxocara seropositivity than that of the non-asthmatic controls (21.2 vs 8.6, P = 0.047), Conclusion: The observed relationship between exposure to Toxocara infection and bronchial asthma in Malaysian children warrants further evaluation. Art understanding of any possible contribution to the pathogenesis of childhood asthma provides a potential avenue for prevention.